(3eYQGL GdfHj Udi Gddg Ydjg hSde QhGjI GHf YHGSs - (3GdbQTj GdgGTej, GHf YHGS, YHO Gddg Hf YHGS Hf YHO GdeWdH, J(B68(3g`s
(3ChdgG (B:s
{(3SHMGf GdPj CSQi HYHOg djdG ef GdeSLO GdMQGe Edi GdeSLO GdCbUi GdPj HGQcfG Mhdg(B}s
(3BNQgG (B:s
(3hfSCd Gddg GdSdGeI aj GdOGQjf ef GdfGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 95s
(3eYLe GdeDdajf(B: 2 / 249s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs